THE EVOLUTION OF AVERAGE PRICES FOR AGRICULTURAL PRODUCTS IN ROMANIA DURING 2007-2017 - Gabriela GIMBĂȘANU; Valentina TUDOR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper analyzes the evolution of the average price for agricultural products in Romania, as compared to the evolution of cereal prices in the European Union, in order to highlight the price differences as well as the causes that generate these differences. Also, this article will highlight the most suitable moments for valorising wheat, barley, corn production. In this paper we have proposed to analyze the evolution of average prices of agricultural products in Romania during the reference period 2007-2019 in order to identify in what trends are the best prices of the year in which the cereals can be sold and what extra income farmers can get by selling grain at the right time when market pressure is low and demand is high.